Profil Self Regulated Learning Siswa SMA “X” di Jember Selama Masa School From Home (SFH) - Anggraeni Swastika Sari; Ria Wiyatfi Linsiya (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2022)
This study aims to provide an overview of Self Regulated Learning for higt school student “X” in Jember during the pandemic. The method used is descriptive quantitative. The research subjects were high school students with a sample of 166 students. The technique used is random sampling using google form. The results of the validity of the Self-Regulated Learning scale are between 0.257 to 0.695 with a reliability value of 0.801. Based on the category, the Self Regulated Learning of higt school student "X" is still in the high category. Judging from the aspect, the highest aspect of metacognitive is 43.98%, while the lowest aspect of motivation is 35.54%. Demographically, it can be seen that female students have higher Self-Regulated Learning while boys have lower. In addition, class XII students and students majoring in science seem to have higher Self-Regulated Learning. This research still has limitations. Further researchers can increase the number of research samples and can use qualitative methods in order to provide a more detailed picture.